On some Parasites of the Lac Insect - Varshney, R. K.; Grivaghey, U. P.; Sundaram, R. M. (Indian Forester, 1967)
Insect parasites from two lac insect species, developing on seven species of plants, were reared. They were found to belong to five species of Hymenopteras Lac insect devoloping on Hibiscus sp, was found specific in its parasitization. Importance of Eupelmus tachardiae and Microbracon greeni has been discussed in relation to their hosts. A new kind of antenna in the females of Parechthrodryinus clavicornis is reported for the first time.